Investigating Emotional Honesty That Effectleader Behavior: A Case Study on Vocational High School Headmaster - Sitanggang, N; Luthan, P.L.A. (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2018)
The objective of the research was to investigate the effects of emotional honesty, interpersonal skills and task structure on directive leader behavior. This research was conducted at Vocational High Schools (SMK) in Medan, using the survey method with 136 principals as population and the sample of 60 principals as respondents who were selected by applying proportional random sampling. The hypotheses were tested by path analysis. This research findings were as follows (1) There was a significantly direct positive effect of emotional honesty on interpersonal skills; (2) There was a significantly direct positive effect of emotional honesty on task structure; (3) There was a significantly direct positive effect of emotional honesty on leader behavior; (4) There was a significantly direct positive effect of interpersonal skills on leader behavior; (5) There was a significantly direct positive of task structure on leader behavior.